2021
DOI: 10.15835/nbha49412509
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression profiling of duplicated flavonoid 3'-hydroxylase gene family in Carthamus tinctorius L.

Abstract: Flavonoid 3′-hydroxylase (F3’H) enzyme is essential in determining the flavonoids B-ring hydroxylation pattern. It is mainly implicated in the biosynthetic pathway of cyaniding-based anthocyanins, flavonols, and flavan-3-ols. However, the evolution and regulatory mechanism of these important flavonoid hydroxylases have not been systematically investigated in safflower (Carthamus tinctorius L.). In this study, we identified 22 duplicatedCtF3'H-encoding genes from safflower through genome-wide prediction and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous studies demonstrated the genome-wide identification of several gene and transcription factor families in safflower. Gene families such as cytochrome P450 [ 30 , 31 , 32 , 33 ], HCT [ 34 ], and oleosin [ 35 ] and transcription-factor-encoding families such as MYB [ 36 ], bHLH [ 37 ], and bZIP [ 38 ] have been extensively studied in safflower. However, the molecular mechanisms underlying flowering control in safflower are still unknown; only a few studies have shown that the yield of petals and seeds of safflowers is related to the number of rosettes and the number of florets in the main and lateral stem, but no information is available on the genome-wide identification and functional analysis of MADS-box genes in safflower.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the genome-wide identification of several gene and transcription factor families in safflower. Gene families such as cytochrome P450 [ 30 , 31 , 32 , 33 ], HCT [ 34 ], and oleosin [ 35 ] and transcription-factor-encoding families such as MYB [ 36 ], bHLH [ 37 ], and bZIP [ 38 ] have been extensively studied in safflower. However, the molecular mechanisms underlying flowering control in safflower are still unknown; only a few studies have shown that the yield of petals and seeds of safflowers is related to the number of rosettes and the number of florets in the main and lateral stem, but no information is available on the genome-wide identification and functional analysis of MADS-box genes in safflower.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 200 compounds have been isolated. Some of these active compounds include alkaloids, quinolones, flavonoids, polyacetylene, safflower polysaccharides, and organic acids, [9][10] with pharmacological effects such as anti-inflammatory, antioxidant, antinociceptive, hepatoprotective, and immunomodulating properties. [11][12][13][14][15] Considering the bioactive compounds, we aim to investigate the therapeutic potential of Carthamus tinctorius L. against TNBS-induced ulcerative colitis in balb/c mice.…”
Section: Introductionmentioning
confidence: 99%